Severe iron deficiency anaemia following bariatric surgery - Manappallil, Robin George (Asian Journal of Medical Sciences, 2016)
The human body stores energy in the fat cells as triglycerides, which when needed gets released as free fatty acids. This physiologic system enables humans to withstand starvation for several months. But this system may get interrupted by genetic factors and sedentary lifestyle, leading to increase adipose energy stores and morbidity or mortality. Obesity is a chronic condition, which may be difficult to treat with therapeutic lifestyle modifications alone, that is diet and exercise. In such cases, bariatric surgery (BS) is an option to lose weight, in order to prevent serious health issues. However, nutritional deficiencies following this surgery have been of great concern. This case report is regarding a young lady who developed severe iron deficiency anaemia (IDA) within 6 months of BS despite taking nutritional supplements. Asian Journal of Medical Sciences Vol.7(4) 2016 110-112